Sistema permanente de avaliação do Ceará: detalhamento da matriz referência de matemática do 9º ano do ensino fundamental - Azevedo, Luiz Felipe Araújo (2022)
This work aims to present a study on the Permanent System of Evaluation of Basic Education in Ceará (SPAECE), focusing on the reference matrix of mathematics for the 9th year of the final years of elementary school. The evaluation characteristics are presented, such as: Reference matrix, item, proficiency scale and descriptors. In the last section, the research reference matrix is ​​detailed, 1 item is presented as an example, exploring the possibilities of thoughts on the part of the students, as well as discussions and strategies to improve the teaching of the Descriptor. The main contributions are referenced by the Secretary of Education of Ceará and by SPAECE itself, either through the website or through the pedagogical bulletins, in addition to several authors on mathematics teaching, assessment and education.